Application of Acoustic Metamaterials in the Design of Muffling Unit of Internal Combustion Engine - Li, Tianshuo; Zheng, Lei; Bi, Zhengyang; Ji, Hongchao (Archives of Acoustics, 2026)
Aiming at the problems of large volume, high exhaust resistance and difficulty in suppressing noise in the 500 Hz to 100 Hz frequency band of traditional internal combustion engine exhaust mufflers, a noise reduction unit design based on acoustic metamaterials is proposed. Based on the equivalent medium theory, an acoustic model with a ring structure and multi-region variable refractive index was established. Phase control is achieved by helically winding the acoustic channel to change the refractive index, and the basic dimensions of the acoustic metamaterial muffling unit are calculated. The sound field distribution, transmission loss and flow field characteristics of the muffling unit are simulated and analyzed. This structure utilizes a multi-layer acoustic channel structure, effectively alleviating the problem of insufficient low-frequency noise elimination caused by the asymmetry of Fano interference. It achieved a transmission loss of over 10 dB within 85 % of the 500 Hz to 1000 Hz frequency band, and still maintained excellent noise reduction performance under high-frequency conditions through multi-level phase control. By connecting multiple units in series, a transmission loss of 10 dB can be achieved within 85 % of the 500 Hz to 1000 Hz frequency band. The exhaust flow field of the muffling unit was simulated and analyzed. Whether used alone or in series with the traditional muffling structure, the exhaust resistance remained within the range of 360 Pa to 370 Pa. Experimental tests show that when the metamaterial muffler unit is used in combination with the traditional muffler, it effectively achieves targeted noise elimination in the 500 Hz to 1000 Hz frequency band, and also demonstrates clear noise reduction capabilities in higher frequency ranges. The high noise suppression characteristics, high gas passage characteristics and compact volume characteristics of this structure provide more potential analysis methods and design schemes for the research and development of internal combustion engine mufflers and noise reduction accessories.